Transcutaneous Neuromodulation for Constipation and Fecal Incontinence in Children: A Systematic Review and Meta-Analysis - Correia, Ronny Rodrigues [UNESP]; Gameiro, Luis Felipe Orsi; Trevisane, Nathalia Grion [UNESP]; Bertanha, Matheus [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (MDPI, 2023)
Introduction: Constipation is a disorder with a multifactorial origin. Constipation has a varied clinical presentation, including infrequent defecation of bulky stools and episodes of retentive fecal incontinence. Neuromodulation has been used to treat many health problems, with promising results. Objective: To conduct a systematic review of randomized clinical trials based on the effects of transcutaneous neuromodulation in treating constipation and retentive fecal incontinence in children and adolescents. Methods: A systematic review of randomized clinical trials was performed. Medline (PubMed), PEDro, SciELO, Cochrane (CENTRAL), Embase, and Scopus databases were searched from March 2000 to August 2022. We included clinical trials evaluating transcutaneous neuromodulation in children with constipation and fecal incontinence compared or associated with other types of treatment. Two reviewers independently selected relevant studies, assessed the methodological quality, and extracted the data. Results: Three studies with 164 participants were included in this review. Two meta-analyses were generated based on these studies. These analyses revealed that transcutaneous neuromodulation is an effective adjuvant treatment modality that improves children’s constipation and retentive fecal incontinence. The methodological quality of the included studies was classified as high based on the assessment of the quality of evidence, with a high degree of confidence based on the GRADE system. Conclusions: Transcutaneous neuromodulation is an effective adjuvant treatment modality for children with constipation and retentive fecal incontinence.
Keywords: children; constipation; fecal incontinence; neuromodulation